Uncertainties about accepting care robots - Turja, Tuuli (Frontiers in Digital Health, 2023)
In the midst of the anticipation of care robots renewing elderly care, care workers are expected to orient themselves in this future, however uncertain. To examine how uncertainty over the appropriateness of care-robot use associates with robot acceptance, different scenarios of robot assistance were presented to a sample of care professionals in two waves 2016-2020. The views of usefulness of robot assistance yielded underlying structures of plausible and implausible care-robot use. The perceived appropriateness of utilizing robots in care was stronger in the plausible robot scenarios. The uncertainty about robots having an appropriate role in care work correlated negatively with the perceived usefulness of robot assistance, but was even highlighted among the scenarios of implausible tasks. Findings further show how uncertainties about care-robot use have been reduced across four years between data collections. In robotizing care work processes, it may be more beneficial to attempt to convince the care workers who are undecided about robot acceptance than to push care-robot orientation to those who strongly oppose care-robot use.